Pengaruh Effective Tax Rate, Bonus Mechanism, Debt To Equity Ratio, Dan Exchange Rate Terhadap Keputusan Transfer Pricing : Studi pada perusahaan sektor industri barang konsumsi yang terdaftar di Bursa Efek Indonesia periode 2011 - 2018 - Dessy Rosmawati; Wajib Ginting (Acman: Accounting and Management Journal, 2022)
The purpose of this study is to examine the Effective Tax Rate, Bonus Mechanism, Debt to Equity Ratio, and Exchange Rate on Transfer Pricing Decisions on 7 Consumer Goods Industrial Sector Companies listed on the Indonesia Stock Exchange for the period 2011-2018. The data used is secondary data. This research method is quantitative with a descriptive verification approach. The population of this research is the consumer goods industry sector as many as 42 companies. The number of samples in this study was seven companies determined using purposive sampling; data collection was carried out through documentation and literature study. This research was tested using model feasibility, overall model test, logistic regression analysis, coefficient of determination test, and hypothesis testing using a partial test (wald test) and simultaneous test (omnibus test). Based on the research results on the Wald test, it found that the Effective Tax Rate did not affect Transfer Pricing Decisions where the significance (sig.) of 0.236 was greater than 0.05. Bonus Mechanism has a significant positive effect on Transfer Pricing Decisions where the significance (sig.) of 0.045 is smaller than 0.05. Debt to Equity Ratio has no effect on Transfer Pricing Decisions where the significance (sig.) of 0.102 is more significant than 0.05. Exchange Rate has no effect on Transfer Pricing Decisions where the significance (sig.) of 0.796 is more significant than 0.05. Based on the research results on the omnibus test, it found that the Effective Tax Rate, Bonus Mechanism, Debt to Equity Ratio, and Exchange Rate simultaneously (together) affected Transfer Pricing Decisions where the chi-square value was 10.285 greater than the chi-square table. 9.48773 and a significance value of 0.036, which is smaller than 0.05. Based on the results of the coefficient of determination of 31.7%, it concluded that the Effective Tax Rate, Bonus Mechanism, Debt to Equity Ratio, and Exchange Rate on Transfer Pricing Decisions are 31.7%. While the remaining 68.3% were influenced by other factors outside this research, such as Tunneling Incentive, Company Size, and Foreign Ownership.